KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SMP AL-KAMIL ISLAMIC BOARDING SCHOOL, KABUPATEN CIANJUR - Acep Nurullah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2024)
Education is essentially a process of knowledge transfer that is carried out gradually, continuously and requires a long process. So in the process it is necessary how to manage so that it can run optimally. The purpose of this study is to determine the managerial competence of principals in improving professional competence and strategies of principals in an effort to improve teacher professionalism at SMP Al-Kamil Islamic Boarding School. This research uses qualitative methods with the process of data collection through observation techniques, documentation studies and interviews. Miles and Huberman are used in conducting data analysis including: presenting data, reducing and drawing conclusions. While the data validity process is inseparable from 4 validation standards consisting of: credibility, transferability, dependability and certainty. The results of the study found that teachers at SMP Al-Kamil Islamic Boarding School have professionally seen the teaching process in class even though it has not run as a whole. The managerial competence of the principal in ensuring teacher professionalism is consciously carried out through planning involving teachers, several activities in supporting teacher professionalism include workshops, training and supervision in an effort to assess teachers related to their responsibilities and responsibilities.